Media Komunikasi Pilihan Generasi Z sebagai Ruang Aman dan Media Ekspresi - Bulan Zerlina Fahlevy; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The development of digital media has encouraged Generation Z to utilize various communication platforms as a means of self-disclosure and privacy management in their interactions. This study aims to understand how Generation Z engages in self-disclosure through Instagram Close Friends and WhatsApp Groups, as well as the reasons behind their preference for these two media. This study uses the theoretical foundations of Computer Mediated Communication (CMC), Communication Privacy Management (CPM), and Theory of Reasoned Action (TRA) to analyze individuals' considerations in choosing digital communication media. This study uses a qualitative approach with a phenomenological method, with data collection through in-depth interviews, observation, and documentation of seven main informants and one expert informant. The results show that the choice of communication media is not random, but is influenced by communication goals, perceptions of privacy security, feature characteristics, and norms of use within the group. Instagram Close Friends is used to selectively share personal stories without the demand for a response, while WhatsApp Group is used for quick two-way conversations, discussions, and direct emotional support. These findings confirm that the compatibility between the nature of the message and the capabilities of the medium is a major factor in Generation Z's self-disclosure preferences. Perkembangan media digital mendorong Generasi Z untuk memanfaatkan berbagai platform komunikasi sebagai sarana self-disclosure sekaligus pengelolaan privasi dalam berinteraksi. Penelitian ini bertujuan untuk memahami bagaimana Generasi Z melakukan self-disclosure melalui fitur Instagram Close Friends dan WhatsApp Group serta alasan yang melatarbelakangi preferensi terhadap kedua media tersebut. Penelitian ini menggunakan landasan teori Computer-Mediated Communication (CMC), Communication Privacy Management (CPM), dan Theory of Reasoned Action (TRA) untuk menganalisis pertimbangan individu dalam memilih media komunikasi digital. Pendekatan yang digunakan adalah kualitatif dengan metode fenomenologi. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi terhadap tujuh informan utama serta satu informan ahli. Hasil penelitian menunjukkan bahwa pemilihan media komunikasi tidak bersifat acak, melainkan dipengaruhi oleh tujuan komunikasi, persepsi terhadap keamanan privasi, karakteristik fitur, serta norma penggunaan dalam kelompok. Instagram Close Friends dimanfaatkan untuk membagikan cerita personal secara selektif tanpa tuntutan respons langsung, sementara WhatsApp Group digunakan untuk percakapan dua arah yang cepat, diskusi, serta dukungan emosional secara langsung. Temuan ini menegaskan bahwa kecocokan antara karakteristik pesan dan kemampuan media menjadi faktor utama dalam preferensi self-disclosure Generasi Z.